PENGARUH DANA PIHAK KETIGA, NON PERFORMING LOAN, DAN CAPITAL ADEQUACY RATIO TERHADAP LOAN TO DEPOSIT RATIO DAN RETURN ON ASSETS PADA SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Ratu Edo, Delsy Setiawati; Wiagustini, Ni Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
ABSTRACT This study aims to determine the effect of Third Party Funds, Non-Performing Loans, and Capital Adequacy Ratio of Loan to Deposit Ratio and Return on Assets. Testing the research hypotheses using path analysis techniques with the help of multiple regression using the tools of SPSS version 18.0 applications. This research was conducted at banking companies listed in Indonesia Stock Exchange 2010-2012. The study population as many as 31 units. Sampling was done by cencus. The results showed that: Third Party Funds has a positive and significant influence on Loan to Deposit Ratio, Non Performing Loan has a negative and no significant influence on Loan to Deposit Ratio, Capital Adequacy Ratio has a positive and significant influence on Loan to Deposit Ratio. Third Party Funds has a positive and significant influence on  Return On Assets, Non Performing Loan has a negative and significant influence on Return On Assets, Capital Adequacy Ratio has a positive and no significant influence on Return On Assets, Loan to Deposit Ratio has a positive and no significant influence on Return On Assets. It is recommended to further research to investigate other banking financial variables that affect the LDR and ROA and the Banking Industry to maintain standards for the provision of financial ratios that have been hinted at by Bank Indonesia
Keywords: Third Party Funds, Non-Performing Loans, Capital Adequacy Ratio, Loan to Deposit Ratio, Return on Assets